Poly (ADP-ribose) polymerases as PET imaging targets for central nervous system diseases - Tong, Jie; Chen, Baosheng; Tan, Peng Wen; Kurpiewski, Stephen; Cai, Zhengxin (Frontiers in Medicine, 2022)
Poly (ADP-ribose) polymerases (PARPs) constitute of 17 members that are associated with divergent cellular processes and play a crucial role in DNA repair, chromatin organization, genome integrity, apoptosis, and inflammation. Multiple lines of evidence have shown that activated PARP1 is associated with intense DNA damage and irritating inflammatory responses, which are in turn related to etiologies of various neurological disorders. PARP1/2 as plausible therapeutic targets have attracted considerable interests, and multitudes of PARP1/2 inhibitors have emerged for treating cancer, metabolic, inflammatory, and neurological disorders. Furthermore, PARP1/2 as imaging targets have been shown to detect, delineate, and predict therapeutic responses in many diseases by locating and quantifying the expression levels of PARP1/2. PARP1/2-directed noninvasive positron emission tomography (PET) has potential in diagnosing and prognosing neurological diseases. However, quantitative PARP PET imaging in the central nervous system (CNS) has evaded us due to the challenges of developing blood-brain barrier (BBB) penetrable PARP radioligands. Here, we review PARP1/2's relevance in CNS diseases, summarize the recent progress on PARP PET and discuss the possibilities of developing novel PARP radiotracers for CNS diseases.